Self References of “Whoever Does Not Attend Jurist" Book as Deliberative Study - محمد علي التميمي, سعد; ستار ساجت الحسيني, أمجد (Journal of College of Education, 2019)
Praise be to Allaah the almighty the most gratious the most generours… This research is an objective study of the personal signs used by the infallible PBUH through the texts contained in the book is one of the most important books of Hadith in the heritage of Ahl al-Bayt (peace be upon him), a book "who does not attend jurist" by Sheikh Sadok sheds light on the use of these signals in its deliberative system Subject to the linguistic system and other deviate from this grammatical linguistic system to the deliberative system in which the speaker and the addressee in terms of understanding and understanding, in which the sentence is not subject to the linguistic system because they are understood according to the contexts of transient language and this research is divided on the topics according to the levels Three (the speaker and the listener present and absent offeree).
Keywords: Ranking of personal signs, Hanson and the term personal signs, Pragmatic Deliberations, The division of Lakove, We for maximization, We for a group, Mn La Yahduruh Alfqyh.